Politics of belonging and alienation: underprivileged communities' experiences of the False Bay Nature Reserve - Breedeveld, Robin (Department of Sociology, 2025)
This thesis examines the experiences of underprivileged local communities surrounding the False Bay Nature Reserve in Cape Town, focusing on their sense of belonging or alienation. Conservation efforts often inhibit local communities' sense of belonging to nature, as they are seen as detrimental to conservation goals. This human alienation from nature conservation is prevalent across Africa due to a history of colonialism, racial discrimination and processes of exclusion. This further marginalises communities already facing spatial, social and economic exclusion in townships. Drawing on a diverse body of literature, this thesis examines concepts of alienation and belonging in human-nature interactions in the False Bay Nature Reserve. It employs qualitative methods, including in-depth interviews and ethnographic methods such as participant observation, to capture local voices and perspectives. The findings indicate that the underprivileged township communities living around the False Bay Nature Reserve experience strong feelings of alienation and non-belonging. Several factors emerged through the study, including the structural and spatial organisation of the nature reserves in the context of the so-called coloured townships; communities' precarious economic circumstances; and deeply rooted identity crises alienating the coloured communities from their heritage and connections to nature. The study, however, also identifies various initiatives that aim to enhance belonging to nature, such as Environmental Education (EE), community organisations, and employment opportunities in the nature reserve. In addition, Rastafarians in the community serve as custodians of both nature and indigenous knowledge, helping to restore the community's relationship with nature and its indigenous identity. This thesis suggests that the lingering colonial legacy of urban nature conservation in Cape Town results in a violent and alienating relationship between nature and surrounding local communities. However, it also identifies community-focused initiatives and pathways for reconciliation. By capturing the experiences of a wide variety of community members, this thesis provides an analysis of deeply personal experiences and informal interpersonal interactions with nature that define belonging or alienation to the nature reserve.